Can markets be developed to promote economic self-reliance of refugees? An evaluation of the promotion of digital financial services in Ethiopia by SHARPE - de Brauw, Alan; Tefera, Mulugeta (International Food Policy Research Institute, 2023)
The Strengthening Host and Refugee Populations in Ethiopia (SHARPE) programme uses a market systems development approach to promote increased self-reliance and economic opportunities for refugees and host communities in three areas in Ethiopia: Jijiga, Dollo Ado, and Gambella. SHARPE aims to generate economic opportunities for refugee hosting communities through the piloting and scaling of interventions across different sectors. This approach is based upon understanding the economic barriers that refugee and host communities face, and working with key stakeholders – including businesses, government, and service providers - to improve market function for both host community members and refugees residing in target communities. SHARPE identified the financial market as a strong target for market systems interventions, based on reforms to the Refugee Proclamation in Ethiopia in 2019 allowing refugees to access telecommunications and banking services. As a result, nascent mobile money platforms aligned with banks could begin to market digital financial services to refugees. As digital financial services had already been growing in Somali region, we focused impact evaluation work around the investments SHARPE was making in the financial market system in the two areas of Somali region (Jijiga and Dollo Ado).